Development of grinding wheel type magnetorheological finishing process for blind hole surfaces. Issue 4 (12th March 2021) - Aggarwal, Ankit; Singh, Anant Kumar
ABSTRACT: Fine finishing of the inner surfaces of the cylindrical blind holed (CBH) components has a rising demand in the manufacturing industries to reduce their frictional characteristics and improve functional efficiency. So, an attempt has been made in the present work to develop a new magnetorheological finishing (MRF) process with a grinding wheel type single magnetic tool for fine finishing the CBH work part surfaces. The main novelty in the proposed work is the grinding wheel type magnetorheological finishing (GWMRF) tool designed with the V-shaped grooves to retain the magnetorheological polishing fluid more strongly. This is because of the edge effect which provides a higher magnetic flux concentration. Also, the present single GWMRF tool operates eccentrically so that different sizes of CBH surfaces can be finished. After the experimentation with the MRF process using optimized parameters, the roughness values reduce from 240 to 90 nm on the longitudinal and 60 from 230 nm on the flat end surfaces of the CBH workpiece utilizing the V-grooved GWMRF tool. The surface characteristics get enhanced significantly. Thus, the present developed process can find its usefulness in industries for fine finishing the CBH workpieces like molds, dies, etc. after the traditional grinding process.